The utilization of censor meals by laying hens - Ong, H. K.; Hutagalung, R. I. (Malaysian Society of Applied Biology, 1978)
The replacement of maize in the diet of laying hens by various levels of Censor meal. a product obtained by mechanical drying of palm oil effluents (sludge) with absorbent feed materials was studied. Two types of Censor meals. namely TK8 and TKG. were used to replace maize In the diets at levels of 25. 5O. 75 and 100%. respectively. Egg production was lower in the Censor-based diets than In the control diet. although the difference was not significant. There was no difference in egg weight as well as other egg quality measurements. Visual observation showed a decrease in egg yolk pigmentation with incrasing levels of Censor meal.